The Malaysian Estates Staff Provident Fund, 1947-2017 Malaysia's oldest provident fund : with an economic, social and political perspective - Jeyaraj C. Rajarao (Strategic Information and Research Development Centre, 2018)
In this book, Jerayaj C. Rajarao provides a detailed and compelling account of the first provident fund established in Malaya through co-operation between plantation companies, the All Malayan Estates Staff Union and the then colonial government of Malaya.